Mesa Redonda: Reforma de la Ley General De Sociedades en el Perú - Hundskopf Exebio, Oswaldo (2017)
How effective is the current General Corporations Law?. Is it necessary to reform the General Corporations Law? What are the main reforms that must be implemented? Should other laws be amended?.This round table, responds to each of these questions and many more, dealing with many controversial issues in commercial and corporate law.